Meta-Analisis Validitas Penggunaan LKPD Terintegrasi STEAM-PjBL untuk Peserta Didik Fase F - Putri, Annisa Nurhidayah; Zulyusri, Zulyusri (Al-Alam: Islamic Science Education Journal, 2025)
The use of valid and high-quality Student Worksheets (LKPD) plays an important role in supporting learning. The STEAM-PjBL (Science, Technology, Engineering, Arts, and Mathematics–Project Based Learning) approach is considered capable of increasing student engagement and 21st-century skills, but studies on the validity of integrated STEAM-PjBL LKPD for phase F students are still limited. This study aims to analyze the validity level of STEAM-PjBL integrated LKPD through a meta-analysis of 10 scientific articles in accredited journals. The analysis was conducted descriptively on the aspects of content, language, and presentation. The results show that the average validity of the content aspect is 90.14%, language 89.90%, and presentation 89.57% with a category of highly valid. Thus, integrated STEAM-PjBL worksheets are declared highly suitable for use in learning.